THE INVESTIGATION OF PRESENT CONTINUOUS TENSE DIFFICULTIES AT NINETH JUNIOR HIGH SCHOOL - Holifah, Agus Regi; Aryadi, Mohammad Fajar; Wahono, Suparwoto Sapto; Hasanah, Uswatun; Sholichah, Laily Fadhilatus (Institut Agama Islam Negeri (IAIN) Bone, 2023)
English learning in Indonesia, especially at the junior high school level has various obstacles. One of these obstacles is that students find it difficult in learning present continuous tense because students think that present continuous tense is similar to present tense. The aimed of this research is to describe students' difficulties in learning present continuous tense. This type of research is descriptive qualitative. The research subjects of this study were 4 students consist of 2 female and 2 male nineth grade students of Al-Fattah Junior High School, Jember The instruments used include observation, interview and document review. The data obtained were analyzed using source triangulation and technique triangulation methods. The results of this study show that students have difficulty in making example sentences using the present continuous tense, difficulty in understanding the meaning of the present continuous tense pattern.